Guest Editorial - Khir,AW; Sherwin,SJ; Pedley,TJ (Proceedings of the Institution of Mechanical Engineers Part H Journal of Engineering in Medicine, 2008)
Over the last 50 years, developments in medical imaging, experimental techniques, and computational power have continued to advance research into physiological fluid dynamics. Almost all the topics covered by the papers in this Special Issue would have been recognizable to the researchers forty years ago, but in (almost all) cases the methods used would not, both for the technical reasons referred to above and for genuine advances in scientific insight. For example, the first two papers are concerned with the arterial pressure and both show, rather surprisingly, that Otto Frank's 1899 Windkessel model is still the best way of relating diastolic arterial blood pressure to the flowrate through the microcirculation; however, the first paper shows that more insight into pulse propagation can be gained from Parker's wave impulse analysis than from the traditional Fourier analysis. It appears that, despite its longevity, pulse wave analysis is not dead and is still capable of providing new insights.